2019
DOI: 10.3389/fmicb.2019.01588
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Dynamics of Yeasts During Vidal Blanc Icewine Fermentation: A Strategy of the Combination of Culture-Dependent and High-Throughput Sequencing Approaches

Abstract: In this study, attention has been focused on the ecology of yeasts during the spontaneous and inoculated fermentation processes of Vidal blanc icewine in northeast China, which is very important for screening autochthonous yeast strains, understanding the roles of these strains, and managing fermentation. The strategies were to conduct spontaneous and inoculated laboratory-scale fermentation processes simultaneously and to analyze the samples taken at different fermentation stages by culture-dependent and -ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…Canonico et al [ 61 ] reported that the concentration of acetic acid in beer produced by mixed fermentation was significantly higher than that produced by pure culture with T. delbrueckii . However, Li et al [ 1 ] reported that C. zemplinina mixed-fermented with S. cerevisiae reduced the ethanol and acetic acid concentrations. In our study, only the acetic acid concentration of wines mixed-fermented with F33 and S. crataegensis YC30 and R. lusitaniae QTX15 increased, whereas it was reduced in other wine samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canonico et al [ 61 ] reported that the concentration of acetic acid in beer produced by mixed fermentation was significantly higher than that produced by pure culture with T. delbrueckii . However, Li et al [ 1 ] reported that C. zemplinina mixed-fermented with S. cerevisiae reduced the ethanol and acetic acid concentrations. In our study, only the acetic acid concentration of wines mixed-fermented with F33 and S. crataegensis YC30 and R. lusitaniae QTX15 increased, whereas it was reduced in other wine samples.…”
Section: Resultsmentioning
confidence: 99%
“…Icewine is a kind of sweet wine that is made by delaying the harvest, allowing the grapes to hang on the vine for a certain period of time, followed by freezing, harvesting, and pressing the grapes at low temperature, and brewing [ 1 ]. Delaying harvesting increases the concentrations of sugars, acids, aroma compounds, and some non-volatile substances in the grapes, intensifying the flavor characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, high alcohol contents were measured in both EF samples, with values of 11.4 ± 0.2 and 13.6 ± 1.3% v/v for years 2016 and 2017, respectively. In contrast, during the spontaneous fermentation process, Saccharomyces dominates later stages of fermentation, whereas non-conventional yeasts can be predominant in the initial and middle stages [ 49 ]. These results support the relevance of the fermentation process over yeast selection, and therefore over the structure of the microbial community [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…paracasei DTA 81 was enumerated on MRS agar supplemented with 135 ppm of natamycin (Merck, Darmstadt, Germany) to prevent the S. cerevisiae growth [7]. S. boulardii 17 was enumerated on the selective Wallerstein Laboratory (WL) agar medium (Oxoid, Basingstoke, UK) [13]. The drop-plate technique was applied for both lacticaseibacilli and yeast enumeration.…”
Section: Microbial Enumerationmentioning
confidence: 99%